2019
DOI: 10.1177/1120700019837943
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes after total hip arthroplasty in extreme elderly patients older than 80 years

Abstract: Background: While extreme elderly patients (age 80 and above) benefit from joint replacement, there is controversy about whether their physical function improves as much as younger individuals following total hip arthroplasty. Methods: We completed a retrospective cohort study comparing extreme elderly total hip arthroplasty (THA) patients to younger patients. We obtained data from a large institutional repository of 2327 consecutive THAs performed from April 2011 through July 2016 at an American academic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The achieved scores [PCS 43.5 (18.5-56.6), MCS 41.8 (30.8-52.3)] are comparable to those reported in the literature for the general population of the equivalent age. [22].…”
Section: Discussionmentioning
confidence: 99%
“…The achieved scores [PCS 43.5 (18.5-56.6), MCS 41.8 (30.8-52.3)] are comparable to those reported in the literature for the general population of the equivalent age. [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines and studies have recommended early surgical treatment within 24–48 hours for patients with hip fracture to relieve pain and to reduce surgery-related morbidity and mortality rates ( 19 , 20 ). Elderly patients were found to have longer hospital stays and higher risks of morbidity and mortality owing to opioid-related and other complications after total joint arthroplasty ( 21 , 22 ). Patients in both the groups in our study had similar mean time to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have begun to use PROMIS instruments in assessment of outcomes related to surgical intervention for different hip pathologies. Clinical studies on outcomes after THA have used PROMIS scores for assessment of both functional outcomes and pain improvement postoperatively . PROMIS instruments have been used in clinical trials assessing baseline disability and functional performance in patients with femoroacetabular impingement (FAI) .…”
Section: Patient‐reported Outcomes Measurement Information Systemmentioning
confidence: 99%
“…Further evaluation of the psychometric properties of PROMIS instruments, specifically for hip pathology, would be beneficial; however, PROMIS instruments have been used in several clinical trials involving THA, FAI, and hip dysplasia . Investigators should take note of the previously reported high floor effects in THA populations .…”
Section: Patient‐reported Outcomes Measurement Information Systemmentioning
confidence: 99%